An Update on Supine Versus Prone Percutaneous Nephrolithotomy: A Meta-analysis - Falahatkar, Siavash; Mokhtari, Gholamreza; Teimoori, Mojtaba (Urology Journal, 2016)
Purpose: To compare results of studies on supine and prone percutaneous nephrolithotomy (PCNL) techniques to find the best position for treating kidney stones. Materials and Methods: A systematic literature review was done in April 2016 using PubMed, Scopus, and Web of Science databases to identify the relevant studies. Article selection was based on the preferred reporting elements of systematic reviews and meta-analysis criteria. A subgroup analysis was done comparing standard prone and supine PCNLs separately. Results: Twenty studies were selected for the analysis including 7733 PCNL cases: 2110 cases were (27.3%) in supine and 5623 cases were (72.7%) in prone position. Supine and prone PCNL had a similar stone-free rate (OR: 0.95; 95% CI: 070-1.27; P = 0.73), operation time (difference in means = -0.01, 95% CI: -0.07 to 0.03; P = .53), hospital stay (differencein means = 0.01, 95% CI: -0.07 to 0.03; P = .52), complication rate (OR: 0.88; 95% CI: 0.76-1.02; P = .09) and urinary leakage (OR: 1.14; 95% CI: 0.50-2.59; P = .75). However, patients received less blood transfusion (OR: 0.72; 95% CI: 0.55-0.94; P = .01) and had less fever rates (OR: 0.65; 95% CI: 0.52-0.80; P < 0.001) in supine PCNL. Conclusion: Supine PCNL has similar stone-free rate, operation time, and hospital stay relative to prone PCNL. However, the supine position has the advantage of less fever and need for blood transfusion. Although both prone and supine PCNLs are suggested for treatment, supine PCNL may have advantages especially in patients with comorbidity.